Z katedr na sztandary. Rozważania o nauczycielach – patronach szkół (na przykładzie Wielkopolski Wschodniej) - Gołdyn, Piotr (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Naming schools is already centuries-old tradition but there is visible development highlighted the most in the twentieth century and it continues till today. Schools for patrons choose usually poets, writers, composers and social workers. Among them there are also former heads of schools and teachers. Considering one of the Polish region which is eastern Wielkopolska, we can mark out eight such characters. Following the decision of teachers, students and parents they became patrons of schools where they once taught. It can be a prove of their great authority among students and local communities. Such a choice of the school’s patron is currently difficult to work with. For students and teachers the character becomes more and more distant and there is no possibility to refer to his work and legacy in many areas.
Keywords: authority; patron; school; teacher